A solution to the inverse problem of mathematical modeling of structural mechanics for beam elements - Purgin, A. A. (AIP conference proceedings, 2016)
The solution of the direct problem of mathematical modeling (DPMM) is a well-studied subject – at present there is a wide variety of software packages aimed at solving it in one degree or another. However, of great practical interest is the inverse problem of mathematical modeling (IPMM), whose solution presents considerably more difficulties than DPMM. Due to the complexity of the IPMM problem, there is currently no software product that can effectively obtain its solution. This study concerns the problem of solving the inverse problem of mathematical modeling in the context of statically indeterminate mechanical systems modeled by finite beam elements.